Improving The Quality of Water for Public Consumption in Dumai City,Riau-Indonesia: Perbaikan Kualitas Air Konsumsi Masyarakat di Kota Dumai - Wetri Febrina; Yusriza; Sirlyana (Journal of Community Service and Application of Science, 2022)
The poor quality of water that’s available in Kota Dumai has forced some people in the community to consume water that didn’t meet health quality standards. As a result, it had an impact on public health, such as skin diseases and diarrhea. Although the government has made efforts to provide clean water through Perusahaan Daerah Air Minum (PDAM), the benefits can’t reach all of society. There were still many people who were forced to consume this poor-quality water. This community service activity aims to educate society about the importance of clean water for health. And train the community to make simple and low-cost water purifiers. As a result, there was an improvement in water quality after the filtering activity, and there was an increase in public knowledge about the importance of clean water for health. In conclusion, this activity really helped the community to get high quality water at low cost